Development of LKPD IPAS Using QR-Code with Discovery Learning Model to Improve Students' Critical Thinking Class V Elementary School - Retna Yupika; Fetri Yeni J; Abna Hidayati; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
This study aims to develop a Science Student Worksheet (LKPD) based on QR-Code using the Discovery Learning model to enhance elementary students’ critical thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed LKPD was validated by material, media, and language experts, resulting in an average validity score of 92%, indicating it is “very valid.” Practicality testing involved teachers and students, yielding scores of 93% and 95%, respectively, which fall under the “very practical” category. The effectiveness of the LKPD was assessed through pre-test and post-test results on students’ critical thinking skills. The average post-test score reached 85.8, showing the LKPD effectively improved students' critical thinking. In addition, students showed high engagement when using the QR-Code feature, which provided easy access to additional digital learning resources. Overall, the QR-Code-based LKPD with the Discovery Learning model is valid, practical, and effective, making it a relevant instructional tool to support active learning and improve the quality of science education in elementary schools.